Peningkatan Mutu Lulusan Siswa SMK Negeri 2 Pandeglang Melalui Pembelajaran Teaching Factory - Irwanto, Irwanto (Penerbit Widina, Widina Media Utama, 2024)
This research aims to obtain policy recommendations regarding the implementation of learning through teaching factories as an effort to improve the quality of student graduates at SMKN 2 Pandeglang. The type of research used is field study which is descriptive analysis. Data collection was carried out using observation techniques, in-depth interviews and documentation studies. The research location is at SMKN 2 Pandeglang, Pandeglang Regency, Banten Province. The research samples were school principals, productive teachers, and teaching factory managers. The research results show that SMKN 2 Pandeglang does not fully understand the function of the teaching factory, as can be seen from weak planning, implementation of learning, production activities and limited industrial collaboration. In this case, the implementation of the teaching factory in learning at SMKN 2 Pandeglang still has little impact on improving the quality of graduates at the vocational school, so that assistance efforts are needed in the teaching factory in the productive learning process, especially the involvement of the industrial world which needs to be optimized.ABSTRAKDalam penelitian ini bertujuan untuk mendapatkan rekomendasi kebijakan dalam pelaksanaan pembelajaran melalui teaching factory sebagai upaya peningkatan mutu lulusan siswa di SMKN 2 Pandeglang. Adapun jenis penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Pengumpulan data dilakukan dengan teknik observasi, wawancara secara mendalam dan studi dokumentasi. Lokasi penelitian di SMKN 2 Pandeglang, Kabupaten Pandeglang Provinsi Banten. Sampel penelitian adalah kepala sekolah, guru produktif, dan pengelola teaching factory. Hasil penelitian menunjukkan bahwa SMKN 2 Pandeglang belum sepenuhnya memahami fungsi teaching factory, tampak dari lemahnya perencanaan, pelaksanaan pembelajaran, kegiatan produksi, dan kerjasama industri terbatas. Dalam hal ini pelaksanaan teaching factory dalam pembelajaran di SMKN 2 Pandeglang masih kurang berdampak terhadap peningkatan mutu lulusan di SMK tersebut, sehingga memerlukan upaya pendampingan dalam teaching factory dalam proses pembelajaran produktif, terutama pelibatan dunia industri yang perlu dioptimalkan.